Biophysical Methods for the Study of Microbial Surfaces - Frases, Susana; Viana, Nathan B.; Casadevall, Arturo (Frontiers in Microbiology, 2011)
The challenge in studying the surface architecture of different microbial pathogens is to integrate the most current biochemical, spectroscopic, microscopic and processing techniques. Individually these methods have insufficient sensitivity to reveal complex structures, such as branched, large, viscous polymers with a high structure hydration, size and complexity. However, when used in combination biophysical techniques are our primary source of information for understanding polydisperse molecules and complex microbial surfaces. Biophysical methods seek to explain biological function in terms of the molecular structures and properties of specific molecules. The sizes of the molecules found in microbial surfaces vary greatly from small fatty acids and sugars to macromolecules like proteins, polysaccharides and pigments, such as melanin. These molecules, which comprise the building blocks of living organisms, assemble into cells, tissues, and whole organisms by forming complex individual structures with dimensions from 10 to 10,000 nm and larger. Biophysics is directed to determining the structure of specific biological molecules and of the larger structures into which they assemble. Some of this effort involves developing new methods, adapting old methods and building new instruments for viewing these structures. The description of biophysical properties in an experimental model where, properties such as flexibility, hydrodynamic characteristics and size can be precisely determined is of great relevance to study the affinity of the surfaces with biologically active and inert substrates and the interaction with host molecules. Furthermore, this knowledge could establish the abilities of different molecules and their structures to differentially activate cellular responses. Recent studies in the fungal pathogen Cryptococcus neoformans have demonstrated that the physical properties of its unique polysaccharide capsule correlate with the biological funct